Poor preoperative patient-reported quality of life is associated with complications following pulmonary lobectomy for lung cancer†. (10th December 2016) - Pompili, Cecilia; Velikova, Galina; White, John; Callister, Matthew; Robson, Jonathan; Dixon, Sandra; Franks, Kevin; Brunelli, Alessandro
Abstract: OBJECTIVES: To assess whether quality of life (QOL) was associated with cardiopulmonary complications following pulmonary lobectomy for lung cancer. METHODS: Retrospective analysis of 200 consecutive patients who had pulmonary lobectomy for lung cancer (September 2014–October 2015). QOL was assessed by the self-administration of the European Organisation for Research and Treatment of Cancer QLQ-C30 questionnaire within 2 weeks before the operation. The individual QOL scales were tested for a possible association with cardiopulmonary complications along with other objective baseline and surgical parameters by univariable and multivariable analyses. RESULTS: Forty-three patients (21.5%) developed postoperative cardiopulmonary complications; 4 of them died within 30 days (2%). Univariable analysis showed that, compared to patients without complications, those with complications reported a lower global health status (GHS) [59.1; standard deviation (SD) 27.2 vs 69.6; SD 20.6, P = 0.02], were older (71.2; SD 8.4 vs 67.7; SD 9.4, P = 0.03), had lower values of forced expiratory volume in one second (FEV1) (83.9; SD 27.2 vs 91.4; SD 20.9), P = 0.06) and carbon monoxide lung diffusion capacity (DLCO) (67.9; SD 20.9 vs 74.2; SD 17.6, P = 0.02) and higher performance score (0.76; SD 0.63 vs 0.53; SD 0.64, P = 0.02). Stepwise logistic regression analysis showed that factors independently associated with cardiopulmonary complications were age [odds ratio (OR) 1.04, 95% CI 1.0–1.09, P = 0.02] and patient-reported GHS [OR 0.98, 95% confidence interval (CI) 0.96–0.99, P = 0.006], whereas other objective parameters (i.e. FEV1, DLCO) were not. The best cut-off value for GHS to discriminate patients with complications after surgery was 50 (c-index 0.65, 95% CI 0.58–0.72). CONCLUSIONS: A poor GHS perceived by the patient was associated with postoperative cardiopulmonary morbidity. Patient perceptions and values should be included in the risk stratification process to tailor cancer treatment.